A GREEN VORTEX-ASSISTED IONIC LIQUID-BASED DISPERSIVE LIQUID–LIQUID MICROEXTRACTION METHOD FOR PRECONCENTRATION AND DETERMINATION OF TRACE CADMIUM IN FOOD SAMPLES - SHEIKH, RAGAA EL; ATWA, MOHAMMED ABDULLAH; ABDULLAH, AMIRA ATEF; ELFETOUH GOUDA, ANDAYMAN ABOU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Green, easy, and sensitive vortex-assisted ionic liquid-based dispersive liquid–liquid microextraction technique (VA-IL-DLLME) was developed to preconcentrate and determine trace quantities of cadmium (Cd2+) ions from real food samples, before detection by flame atomic absorption spectrometry. Methods: The proposed technique base on the utilization of IL (1-hexyl-3-methylimidazolium tris(pentafluoroethyl)trifluorophosphate) as an extraction solvent for Cd2+ ions after the complexation with 2-(2’-benzothiazolylazo) chromotropic acid at pH 8.0. The impact of different analytical parameters on microextraction efficiency was investigated. The validation of the proposed procedure was verified by the test of certified reference material (SRM spinach leaves 1570A) applying the standard addition method. Results: In the range of 1.0–300 μg/L, the calibration graph was linear. Limit of detection, preconcentration factor and the relative standard deviation (RSD%, 25, 150, and 250 μg/L, n=5) were 0.2 μg/L, 100, and 2.0–3.2%, respectively. Conclusion: Green, VA-IL-DLLME method was developed and applied to preconcentrate and determine of trace quantities of Cd2+ in real food samples with satisfactory results. The obtained recovery values showed good agreement with the certified values.